2017
DOI: 10.15560/13.5.635
|View full text |Cite
|
Sign up to set email alerts
|

New locality record of Discothyrea neotropica (Bruch, 1919) (Hymenoptera, Formicidae) for Argentina and remarks on its distribution

Abstract: We collected a queen specimen of Discothyrea neotropica Bruch, 1919 in a pitfall trap in Paititi Natural Reserve, southeastern Buenos Aires province, Argentina. The new record represents the southernmost occurrence for this species and extends its habitat preferences to a humid temperate climate. Our record of D. neotropica is the first in Argentina since 1949.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results suggest that this species occurs in fragments of the Atlantic Forest with a heterogeneous adjacency and a higher percentage of native Atlantic Forest vegetation. However, Arcusa & Cicchino (2017) reported that D. neotropica also inhabits pastures in the Pampas Region, which are considered areas of low environmental complexity.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that this species occurs in fragments of the Atlantic Forest with a heterogeneous adjacency and a higher percentage of native Atlantic Forest vegetation. However, Arcusa & Cicchino (2017) reported that D. neotropica also inhabits pastures in the Pampas Region, which are considered areas of low environmental complexity.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding ant composition, it is important to note that although most species are common in the three areas, like Pseudomyrmex pallidus (Smith, F., 1855), Trachymyrmex fuscus Emery, 1834 and Dorymyrmex brunneus Forel, 1908, for example, occurred only in area 3, which indicates that these species have a high resistance to impacts such as the fire in the Cerrado. Indeed, the genus Dorymyrmex Mayr, 1866 was previously associated with disturbed areas and with little vegetation cover (CUEZZO; GUERRERO, 2012;ARCUSA, 2017), while there are no records for the other species (TABLE 1). Moreover, in the area, 2 the occupancy of some generalists genera such as Mycocepurus, Crematogaster, Ondontomachus, and Pachycondyla, indicates a recovery of the previous conditions of this habitat after four months of the disturbance, since these species need specifics resources such as fruits, nectar, carcasses, and seed arils to survive (BACCARO et al, 2015).…”
Section: Discussionmentioning
confidence: 99%